IMPLEMENTASI PROGRAM ELEKTRONIK KINERJA (e-kin) DI DINAS KOPERASI, USAHA KECIL DAN MENENGAH DAERAH PROVINSI SULAWESI UTARA - Sari Paulina Haloho; Florence D. J. Lengkong; Jericho D. Pombengi (JURNAL ADMINISTRASI PUBLIK, 2023)
Abstract To facilitate the management of employee performance, assess work performance and make it easier to carry out the function of superior control over their subordinates. So the North Sulawesi provincial government implemented the Electronic Performance (e-performance) program within the North Sulawesi government. E-performance is a web-based application system that is used to support and facilitate the implementation of the performance of civil servants (PNS) in recording and reporting work responsibilities. The goal of this research is to learn about and describe the implementation of the e-performance (e-kin) program in the North Sulawesi Province Office of Cooperatives, Small and Medium Enterprises. By using descriptive qualitative research methods. Its data retrieval techniques; techniques of observation, interviews, and the use of documents. The study's findings indicate that while the implementation of the e-performance (e-kin) program in the North Sulawesi Province's Office of Cooperatives, Small and Medium Enterprises has been successful, there is still room for improvement, particularly in the area of infrastructure resources. Where, the internet, which is one of the facilities of the e-performance program at the Office of Cooperatives, Small and Medium Enterprises in the North Sulawesi Province, still occurs frequent network disruptions. Keywords: Implementation, Program, E-Performance.